Association Between Hemoglobin-to-Red Blood Cell Distribution Width Ratio and 30-Day Mortality in Patients with Acute Pancreatitis: Data from MIMIC-III and MIMIC-IV - Xiong, Jihao; Tan, Hongchun; Mao, Shanlin; Ma, Lingfang; Ma, Ke (Turkish Journal of Gastroenterology, 2024)
Background/Aims: To investigate the relationship between hemoglobin-to-red blood cell distribution width (RDW) ratio (HRR) and the 30-day mortality risk in acute pancreatitis (AP), and assess the predictive ability of HRR. Materials and Methods: Data from 2001 to 2019 in the Medical Information Mart for Intensive Care-III/IV (MIMIC-III/IV) were analyzed. The outcome of this retrospective cohort study was 30-day mortality. Hemoglobin-to-RDW ratio (0-24 hours) and HRR (24-48 hours) were divided into 4 groups based on quartiles (Q1, Q2, Q3, and Q4). The predictive effect was evaluated by the C-index. Results: A total of 1736 patients were included, and 30-day mortality occurred in 204 (11.75%) patients. Compared with Q1 of HRR (0-24 hours), Q2 (HR = 0.60, 95% CI : 0.42-0.86), Q3 (HR =0.47, 95% CI : 0.31-0.71), and Q4 (HR = 0.45, 95% CI : 0.29-0.68) of HRR levels reduced the 30-day mortality risk. Hemoglobin-to-RDW ratio (24-48 hours) was consistent with the results of HRR (0-24 hours). For changes in HRR, Q4 for changes in HRR levels (HR = 1.64, 95% CI : 1.09-2.45) increased the 30-day mortality risk. Hemoglobin-toRDW ratio significantly improved the predictive effect of Sequential Organ Failure Assessment (C-index = 0.736) and Bedside Index of Severity in Acute Pancreatitis (C-index = 0.704) on 30-day mortality. Conclusion: Higher HRR levels reduced the 30-day mortality risk in AP and may improve the prediction of other tools. Cite this article as: Xiong J, Tan H, Mao S, Ma L, Ma K. Association between hemoglobin-to-red blood cell distribution width ratio and 30-day mortality in patients with acute pancreatitis: Data from MIMIC-III and MIMIC-IV. Turk J Gastroenterol. 2024;35(8):651-664.